STRATEGI SMP LABSCHOOL UNESA 1 SURABAYA DALAM MENGHADAPI PERUBAHAN KEBIJAKAN PPDB - Rahma Maulida (Universitas Widya Kartika Surabaya, 2024)
The existence of a zoning system in Public Junior High Schools gets impact in Private Junior High Schools especially in a decrease in the number of new student admissions. Likewise, Junior High School of Labschool Unesa 1 Surabaya has experienced a decrease in the number of students, but in recent years the school has experienced an increase in the number of students although the number is not comparable to the previous decrease. The researcher intends to analyze the school's strategy by formulating the problem, Namely